2022
DOI: 10.1111/socf.12776
|View full text |Cite
|
Sign up to set email alerts
|

“I Don’t Want Everybody to Vote”: Christian Nationalism and Restricting Voter Access in the United States

Abstract: Though the persistence of voter suppression and disenfranchisement in the US is welldocumented, we still know little about their contemporary ideological underpinnings beyond partisanship and racial resentment. Highlighting the Christian Right's influence in driving antidemocratic sentiment in the post-Civil Rights era, we propose contemporary ideological support for restricting the vote generally, and specifically, to those who prove "worthy," is undergirded by a pervasive ideology that cloaks authoritarian e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…If Black or Hispanic Americans tend to think of "patriotism" as working toward a more just and equitable society, while Whites see it more as unquestioned loyalty (Perry and Schleifer 2023), it is possible Christian nationalism inclined them to support a qualitatively different idea of patriotic education than for white Americans (see also Perry, Whitehead, and Grubbs 2023). Previous research has found that Black Americans, and occasionally Hispanic Americans as well, score quite differently on outcomes compared to white Americans as Christian nationalism increases (Gorski and Perry 2022;Perry and Schleifer 2022;Perry and Whitehead 2019;Perry et al 2022aPerry et al , 2022bPerry et al , 2022cPerry et al , 2023. Future research must therefore be more careful to unpack the meaning of Christian nationalism and patriotism for respondents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If Black or Hispanic Americans tend to think of "patriotism" as working toward a more just and equitable society, while Whites see it more as unquestioned loyalty (Perry and Schleifer 2023), it is possible Christian nationalism inclined them to support a qualitatively different idea of patriotic education than for white Americans (see also Perry, Whitehead, and Grubbs 2023). Previous research has found that Black Americans, and occasionally Hispanic Americans as well, score quite differently on outcomes compared to white Americans as Christian nationalism increases (Gorski and Perry 2022;Perry and Schleifer 2022;Perry and Whitehead 2019;Perry et al 2022aPerry et al , 2022bPerry et al , 2022cPerry et al , 2023. Future research must therefore be more careful to unpack the meaning of Christian nationalism and patriotism for respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of racial identity moderating this association must be considered. As already discussed, researchers find views of patriotism are differentially shaped by racialized experiences (Parker 2009;Phillips 2018) Perry et al 2022aPerry et al , 2022bPerry et al , 2022cPerry et al , 2023 finds Christian nationalism's association with Americans' views on racial inequality, economics, and authoritarian violence are highly racialized. Directly relevant to this study, Christian nationalist ideology also seems to incline white Americans toward different orientations to patriotism than Black and Hispanic Americans (Perry and Schleifer 2022).…”
Section: Social Dominance Legitimizing Myths and Christian Nationalismmentioning
confidence: 98%
“…We conclude by noting that although we have focused on theoretical and empirical concerns, the aims of prominent QCN literature are also explicitly normative. QCN scholars state that Christian nationalism is a threat to a pluralistic society that must be countered with a coordinated response (e.g., Perry et al 2022). We believe that establishing better delineated boundaries around the concept will serve this end.…”
Section: Discussionmentioning
confidence: 99%
“…The more expansive understanding of Christian nationalism currently in use is counterproductive from both an analytical and normative perspective. In a recent QCN study, Perry et al (2022) stated, first, that “over half of the United States population embraces Christian nationalism to some extent,” and shortly thereafter, that “Christian nationalism is and will continue to be an existential threat to the democratic process” (p. 20). It seems to follow, paradoxically, that American democracy can be secured only if the political will of more than half of the electorate is decisively thwarted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation